NORTH OSSETIA-ALANIA: RELIGION IN THE AXIOLOGICAL STRUCTURE OF ITS POPULATION - GABUEVA, Anjela (CENTRAL ASIA AND THE CAUCASUS, 2020)
In the last few decades, society in the Russian Federation has been exposed to globalization apparent in all spheres of social life ranging from the economy to worldviews. The globalization processes led to the revival of religion and the consolidation of its positions. The role of religion in the life of the peoples living in Russia varies. The Russian Federation is a state with a diverse ethnic composition, different geographical, climatic conditions and history, a state structured around various religious denominations.In the 1990s, the religious policy in Russia was fairly ambiguous and vague, to say the least. This was the time when religious institutions acquired new social roles that moved religion to the fore. It regained its lost positions, the statuses of the previously discriminated religious organizations were restored, while previously unheard-of religious movements spread far and wide across the country.The growing number of religious institutions, their greater role in everyday life of different peoples, the ever increasing authority of their leaders and the emergence of new, non-traditional organizations have created an absolutely new spiritual environment. These processes differ between regions, which means that the state should establish a well-balanced religious policy by taking local speci other things.Religion and religious ideologies are realized on the basis of the altered functions and statuses of religions and the behavior of the followers of different religious organizations.The steadily growing impact of religion in the Northern Caucasus demands closer attention to the transformations of religious beliefs in the context of the social and political statuses of the North Caucasian republics in the Russian Federation.This article is based on the materials of the large-scale polls of the population of the republics of the North-Caucasian Federal District of the Russian Federation: North- Ossetia-Alania, Chechnia, Karachaevo- Cherkessia, Ingushetia, Daghestan and Kabardino-Balkaria carried out in the summer of 2016 by the North-Ossetian Department of Social Studies of the Institute of Socio-Political Research, Russian Academy of Sciences, and the Department of Sociology of the Khetagurov North-Ossetian University which involved 1,200 respondents, including 50 experts (journalists, academics, bureaucrats, members of political parties, people working in the sphere of culture, followers of different religions and legal professionals).